2022
DOI: 10.1002/slct.202203181
|View full text |Cite
|
Sign up to set email alerts
|

Operation Strategy for Avoiding Oiling‐Out During the Anti‐Solvent Crystallization Based on Ternary Phase Diagram

Abstract: Oiling-out occurs during the crystallization process and frequently cause deterioration of the characteristics of crystalline particles. In this study, operation strategies to avoid the oiling-out in the anti-solvent crystallization are investigated based on the ternary phase diagram. It is found that oiling-out could be avoided by designing the trajectory of the operation point on the ternary phase diagram during the anti-solvent crystallization. Additionally, the characteristics of crystalline particles is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[58,59] Moreover, the solute has a structure with more hydroxyl groups, and the lower melting point is more likely to lead to oilingout. [60,61] Take reaction crystallization as an example. On the one hand, the relative molecular mass of the final product can be reduced by choosing a ligand with low molecular weight.…”
Section: Solutementioning
confidence: 99%
See 2 more Smart Citations
“…[58,59] Moreover, the solute has a structure with more hydroxyl groups, and the lower melting point is more likely to lead to oilingout. [60,61] Take reaction crystallization as an example. On the one hand, the relative molecular mass of the final product can be reduced by choosing a ligand with low molecular weight.…”
Section: Solutementioning
confidence: 99%
“…So, the greater the proportion of good solvent and the lower the initial concentration of solute will more likely avoids oilingout. [60] Al-Hanafi et al [54] showed that oiling-out can be avoided by controlling the initial concentration of indomethacin by analyzing the ternary phase diagram of indomethacin in a mixed solvent of DMSO and water. Lu et al [61] found that with idebenone at lower initial concentrations, oiling-out did not take place and the crystallization product had a higher purity.…”
Section: Concentrationmentioning
confidence: 99%
See 1 more Smart Citation